Редуцированные гласные в египетском языке VII в. до н. э. - Вaссоeвич, A. Л.
Vassojevic, A. L., Reduced Vowels in the Egyptian language, 7th Century B.C.; Engl. Résumé; nach assyrischen keilschriftlichen Übersetzungen ägyptischer Personennamen.